Effect of core training on the motor median and ulnar nerve conduction velocity in basketball players - Çuvalcioglu, C.; Soslu, R.; Makaraci, Y.; Dogan, A. A. (International Journal of Applied Exercise Physiology, 2020)
Performance of the movements in the upper extremities, specifically used intensively in basketball, depends on the level of strength and coordination of the muscles located in that area. In this regard, the present study aims to investigate the effect of core training on themedian and ulnar nerve conduction velocity (NCV) in basketball players. Ten male basketball players (avg. age: 18.4±0.78 years, height: 191.6±8.65 cm, weight: 80.9±10.15 kg) were participated in the study voluntarily. Core training program was applied to athletes for 8 weeks, 3 days a week, and 30-45 minutes per session. Median and ulnar NCV measurements were performed before and after the training program (pre-and post-test). For the analysis of the pre-and post-test, the MANOVA test was used, and the probability value of p<0.05 was considered statistically significant. No statistical differences were observed in the dominant hand motor median and ulnar NCV measurements after the core training (p>0.05). A statistical difference was found only in the "distance" parameter in the non-dominant hand median and ulnar NCV measurements (p<0.05). As a result, 8 weeks of core training in basketball players was found to have no effect on the dominant and non-dominant hand NCV values. In further studies, changes in NCV in different exercise protocols and sports branches can be investigated to identify the parameters and chemical changes that are believed to have an effect.